Spatial patterns, hotspot, and risk assessment of heavy metals in different land uses of urban soils (case study: Malayer city). Issue 1 (2nd January 2018) - Solgi, Eisa; Oshvandi, Zahra
ABSTRACT: A study on identification of hotspots, spatial patterns, and risk evaluation of heavy metals in urban soils of Malayer city (Iran) was carried out. Fifty-nine composite surface soil samples were collected from six different land uses (urban parks, streets, and squares, boulevards, residential and agricultural areas) in Malayer city, and the total heavy metals were measured by atomic absorption spectroscopy. Average concentrations of Cd, Pb, Cu, and Zn, As, Cd, and Pb were 0.66, 15.51, 12.25, and 96.8 mg/kg, respectively. Among the six land uses, heavy metal contamination was heavier for street, while low contamination could be found for residential and urban parks. The spatial distribution of Pb in surface soil was similar to those of Cd, and Cu was similar to those of Zn with decreasing values from the central areas to the suburb. Also, there were several hotspots for studied heavy metals that Cd and Pb were mainly occurred in locations of heavy traffic in the city center and Cu and Zn in the west and northwestern in the city. The calculated result of risk evaluation showed that much of the city suffered from moderate to severe pollution by four of these heavy metals.